Biomimetic Scaffolds with a Mineral Gradient and Funnel‐Shaped Channels for Spatially Controllable Osteogenesis. Issue 9 (29th May 2021) - Qiu, Jichuan; Ahn, Jaewan; Qin, Dong; Thomopoulos, Stavros; Xia, Younan
Abstract: A facile method is described herein for generating a mineral gradient in a biodegradable polymer scaffold. The gradient is achieved by swelling a composite film made of polycaprolactone (PCL) and hydroxyapatite (HAp) nanoparticles with a PCL solution. During the swelling process, the solvent and PCL polymer chains diffuse into the composite film, generating a gradient in HAp density at their interface. The thickness of the mineral gradient can be tuned by varying the extent of swelling to match the length scale of the natural tendon‐to‐bone attachment (20−60 µm). When patterned with an array of funnel‐shaped channels, the mineral gradient presents stem cells with spatial gradations in both biochemical cues (e.g., osteoinductivity and conductivity associated with the HAp nanoparticles) and mechanical cues (e.g., substrate stiffness) to stimulate their differentiation into a graded distribution of cell phenotypes. This new class of biomimetic scaffolds holds great promise for facilitating the regeneration of the injured tendon‐to‐bone attachment by stimulating the formation of a functionally graded interface. Abstract : A controllable gradient in mineral content is created in a biodegradable scaffold by swelling a hydroxyapatite/polycaprolactone composite film with a polycaprolactone solution. The scaffold is used to stimulate the graded differentiation of stem cells and thus mimic the gradient in cell phenotype found at the natural tendon‐to‐bone attachment. ​